Optimizing content graphene oxide in high strength concrete (International Journal of Scientific Research and Management (IJSRM), 2016)
This paper describes research advances in the field of nanomaterials, which represents a valuable opportunity for developing compounds nanoscale materials, such as graphene oxide, the effect of the incorporation of nanomaterials disclosed in low doses for increased resistance in the concrete, better hydration and improve the microstructure and mechanical properties of the concrete